2018
DOI: 10.1016/j.ijporl.2018.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcome of childhood nasopharyngeal carcinoma: A single institution experience

Abstract: Multimodal therapy of children with nasopharyngeal carcinoma is associated with long-term survival. It is expected that further advances in the management of these patients, with improved radiotherapy and chemotherapy, will reduce acute and late toxicity and improve quality of life of treated children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…We have shown that IMRT resulted in a favorable prognosis for children and adolescent NPC (5-year DFS, 81.5%), especially in patients with low pretreatment EBV DNA load (5-year DFS, 86.9%), which indicated that pretreatment EBV DNA level is an important prognostic factor in this age group. In young patients, the predominant histology of NPC is an undifferentiated variant of disease (27)(28)(29), which was confirmed in our study where 98.0% of pediatric patients were histologically WHO type III. On the other hand, ∼96.0% of our patients presented in advanced clinical stage III or IV, similar to other reports with stage III-IV patients accounting for 92.0-97.3% (5,7,29).…”
Section: Discussionsupporting
confidence: 87%
“…We have shown that IMRT resulted in a favorable prognosis for children and adolescent NPC (5-year DFS, 81.5%), especially in patients with low pretreatment EBV DNA load (5-year DFS, 86.9%), which indicated that pretreatment EBV DNA level is an important prognostic factor in this age group. In young patients, the predominant histology of NPC is an undifferentiated variant of disease (27)(28)(29), which was confirmed in our study where 98.0% of pediatric patients were histologically WHO type III. On the other hand, ∼96.0% of our patients presented in advanced clinical stage III or IV, similar to other reports with stage III-IV patients accounting for 92.0-97.3% (5,7,29).…”
Section: Discussionsupporting
confidence: 87%
“…A meta-analysis by Langendijk et al demonstrated that concurrent chemotherapy was associated with a pooled hazard ratio (HR) of 0.48 (95% CI, 0.32-0.72) which corresponded to a 20% improvement in five-year OS compared to RT alone while neoadjuvant chemotherapy was associated with improved locoregional control with a decreased rate of distant metastases [100]. Similar results have been documented throughout the literature [101][102][103][104][105]. Despite these advances, many patients continue to present with locoregional or systemic recurrence with most relapses occurring within the first two years (median 8 months) following treatment [98,106,107].…”
Section: Nasopharyngeal Carcinomamentioning
confidence: 57%
“…Radiation of 50 Gy is often desirable for neck nodes. The chemotherapy includes methotrexate, bleomycin, and cisplatin [17]. Nasopharyngeal carcinomas are more radiosensitive [18].…”
Section: Discussionmentioning
confidence: 99%